DID COVID-19 INCREASE THE RISK OF INTERNAL AUDITING? - Hans-Ulrich Westhausen (Economic Review)
For about three years now, the COVID-19 pandemic has kept the global economy on tenterhooks. Although the pandemic has now been declared "over", the consequences of this mega-example of disruptive developments are still being felt everywhere, also regarding the work of Internal Audit. In particular, the spatial and personnel distance from operational activities due to lockdown and home office raise the question of whether these serious changes in the audit environment have possibly also changed the audit risk. This paper attempts to address this question using the Audit Risk Model (ARM) and a survey of audit experts to operationalize a comparison of audit risk before and after COVID-19. The results suggest that the pandemic has significantly changed the audit environment and, moreover, is expected to increase audit risk. As a result, Internal Audit needs to react promptly to adapt its effectiveness to the increased requirements and thus be able to fulfill its responsibility as a "third line" of corporate governance in the future.